Brown & Cottrell, Modern America Lives - Individuals And Issues In American History Since 1945 - Newman, Louise (Teaching History: A Journal of Methods, 2008)
Modern American Lives was conceived as a college text, meant to supplement the usual survey textbooks. It is composed of thirteen chapters, each focused on two individuals and a key issue. The chapters are grouped into three chronological sections (1945-60, 1960-80, and 1980-present) and cover a broad range of topics: national politics, foreign policy, social and political activism, popular and literary culture, sports, and business. Each chapter is nicely set up by a two-page overview and ends with useful study questions and a selected bibliography.